Penyelesaian Wanprestasi Perjanjian Kredit Dengan Jaminan Hak Tanggungan - Sutan Ahmad Sayuti Hasibuan (Inovasi Pratama Internasional. Ltd, 2022)
To further secure the funds distributed by the bank (creditor) to the borrower (debtor), security is needed in the form of a guarantee. The collateral that is widely used is land security based on the consideration that land is the safest and has a relatively high economic value. The formulation of the problem in this study is how the legal arrangements for credit agreements with mortgage guarantees at the Kusuma Arta Jaya savings and loan cooperatives occur, if there is a dispute how to resolve them and how are the legal considerations of the judges in the credit agreement with guaranteed mortgage rights at the Kusuma Arta Jaya savings and loan cooperatives in Decision No. 3209 K/Pdt/2020. The method used is normative juridical with a law approach and a case approach. The legal arrangement for credit agreements with mortgage rights is Article 6 of Law no. 4 of 1996 concerning Mortgage Rights. Settlement of disputes in credit agreements with mortgage guarantees at Kusuma Arta Jaya savings and loan cooperatives is to first take several approaches to customers such as billing by telephone or visiting the debtor's house to ask for his achievements. The bank will execute the mortgage object by auctioning the mortgage object through the KPKNL or selling it under the hands of the bank's agreement as the creditor with the debtor. The results showed that the judge's legal considerations in the credit agreement with guaranteed mortgage rights at the Kusuma Arta Jaya savings and loan cooperative in the Supreme Court's Decision Number 3209 K/Pdt/2020 were the debtor had not paid or had stopped paying his credit installments and had 3 (three) ) times giving a written warning letter to the debtor.